Antenna array design with rectangular ring slot for 5G technology - Nur Ilham Aliyaa Ishak; Norhudah Seman; Tien Han Chua (Universitas Ahmad Dahlan, 2019)
A patch antenna with rectangular-shaped ring slot that fed by a coaxial probe is proposed in this article as the single element for planar patch array antenna design to meet the requirement of multiple input multiple output (MIMO) in fifth generation (5G) technology. Initially, the single antenna element is designed at three different center frequencies of 0.85, 1.9 and 2.6 GHz to cover the mobile operating frequency of 0.8, 0.85, 0.9, 1.8, 2.1 and 2.6 GHz, which considering the proposed 5G spectrum below than 6 GHz. The rectangular-shaped ring slot is introduced to the patch antenna with the partial ground plane to widen the bandwidth performance. The designed single element is then arranged to design planar arrays of 2 x 2. Each of elements in the planar array is fed by a coaxial probe. The designs are utilizing a high-performance substrate, Rogers 6010LM.